ENVIRONMENTAL PROBLEMS AND ENVIRONMENTAL VALUES - Barman, Mamta (International Journal of Research -GRANTHAALAYAH, 2015)
The real wealth of any nation and any region lies in the wellbeing of its people. The three main problems in the world, are known as three-P-Population, Poverty, and Pollution. Pollution is the main problem of the modern world. The technological inventions and progress has over powered nature, it has also resulted in the thoughtless exploitation of nature. Awareness by educating everyone, to value the nature and maintain the natural environment are important need. A study was conducted a 50 private and govt. female school students to measure the environmental values. Environmental Value Test (Shrivastav& Dubey, 1995) was used to assess the environmental value of the sample age range varied from 16-17 yrs. Findings of the study reveal that there is degree of high environmental value among both urban groups. Eco-club, Vanmahotsava, Exhibitions are popular means of creating awareness about environment. The need of the hour is to discuss environmental issues as our environmental issues, at global level as a sense of duty. To protect the environment from the adverse effects of pollution, many nations worldwide have enacted legislation to regulate various types of pollution to mitigate their harmful effects.